Compressed Stabilised Earth as Load Bearing Interlocking Block - Nasly, Mohamed Ali (Penerbit UMP, 2010)
The rising costs of construction materials and the need to adhere to sustainability, alternative construction techniques and materials are being sought. Earth as a construction material has been used worldwide since thousands of years. Many methods have been used to produce earth blocks varying according to local climate and environment as well as local traditions and customs. Compressed earth stabilised with cement can be produced by special high compacting pressure machines. Tests have been carried out to get the optimum mix to give the required strength as compressed stabilised soil hollow blocks. The blocks are intended as modular elements in the construction of walls using the load bearing interlocking block technique.